The Feed the Future Rwanda Orange-fleshed Sweetpotato (OFSP) for Income and Nutrition Activity - International Potato Center (2018)
By the end of the third year, the project has directly reached 207,267 households with OFSP and other 144,105 households indirectly in partnership with the Government of Rwanda and other partners. Decentralized vine multipliers (DVMs) have sold vines worth US $411,529. Farmers have sold sweetpotato roots worth US $114,250. It is estimated that the beneficiaries reached by the project have produced and consumed 14,296 tons of OFSP roots.